2016
DOI: 10.2527/jas.2016-0760
|View full text |Cite
|
Sign up to set email alerts
|

Anethol, cinnamaldehyde, and eugenol inclusion in feed affects postweaning performance and feeding behavior of piglets1

Abstract: The early exposure of the fetus to certain volatiles may result in a further preference for these compounds later in life and could positively affect the acceptance of feed containing a similar flavor and the zootechnical responses. The study consisted of 2 trials to determine if including Fluidarom 1003 (a commercially flavored feed additive containing >25% anethol and cinnamaldehyde and >10% eugenol; Norel S.A., Madrid, Spain, Spain) in sow and postweaning piglet diets 1) provokes the presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 31 publications
6
37
1
Order By: Relevance
“…Therefore, eugenol has the potential to be an alternative to AGP, by preventing and alleviating the inflammatory gut diseases caused by weaning stress. Additionally, the flavor of eugenol in feeds positively affects postweaning performance and A c c e p t e d M a n u s c r i p t 6 feeding behavior of piglets, which helped piglets adapt to a novel solid food from liquid (Blavi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, eugenol has the potential to be an alternative to AGP, by preventing and alleviating the inflammatory gut diseases caused by weaning stress. Additionally, the flavor of eugenol in feeds positively affects postweaning performance and A c c e p t e d M a n u s c r i p t 6 feeding behavior of piglets, which helped piglets adapt to a novel solid food from liquid (Blavi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the current study suggest that early feeding experiences can have long-lasting effects on feed preferences, at least up to two weeks after the treatments were not reinforced anymore. Our findings are consistent with previous studies, who also reported differences in short-(during dietary treatment) and long-term feeding preferences (after end of dietary treatments) in piglets exposed to different diets early in life (Figueroa et al, 2013;Blavi et al, 2016;Clouard et al, 2016).…”
supporting
confidence: 93%
“…The balance between aversion and acceptance of flavoured creep feed in piglets seems complex, as feed intake of either a familiar or unfamiliar flavour is variable (e.g. Langendijk et al, 2007;Figueroa et al, 2013;Blavi et al, 2016). These inconsistent results indicate that it is hard to predict whether a flavour increases acceptance of the feed or results in aversion and reduced feed intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the transfer of PC such as anethole, cinnamaldehyde, eugenol [25], limonene and carvone [15] from the feed to amniotic uid of sows during gestation, with effects on reproductive performance and mammary secretions [14], as well as, the antioxidant status in gestating sows [26]. The results of the present study are in line with such ndings with the relative increase of BPC limonene, anethole, borneol, p-cymene, and eucalyptol in the sow's amniotic uid compared to the Control group.…”
Section: Prenatal Effects Of Bpc On Sows and Their Offspringmentioning
confidence: 99%